Enhanced diffusion and mobile fronts in a simple lattice model of glass-forming liquids. Issue 39 (21st October 2015) - Tito, Nicholas B.; Milner, Scott T.; Lipson, Jane E. G.
<x xml:space="preserve">Abstract</x> Diffusion of mobility in bulk and thin film fluids near their glass transition is examined with a kinetic lattice model, and compared to recent experiments on bulk liquids and vapor-deposited thin film glasses.